(untitled) (The Review of Diabetic Studies, 2025)
Aim of the study: This case report examines the therapeutic potential of integrating Jadamayadi Shirodhara with Mantra Music for the management of pre-hypertension, and frequently remains undiagnosed. While modern pharmacological interventions effectively lower blood pressure, they often do not address the underlying systemic risk factors or prevent long-term cardio-cerebrovascular complications as comprehensively as holistic approaches. Consequently, there is a growing interest in integrating traditional Ayurvedic therapies, such as Shirodhara, with non-pharmacological modalities like music therapy to target the multifactorial etiology of pre-hypertension through stress reduction and autonomic nervous system regulation. Methodology: The methodology employed in this case involves a detailed assessment of physiological parameters before, during, and after the intervention to determine the extent of therapeutic benefit derived from this integrative approach. The present single case study was conducted in July 2025 at the G S Ayurveda medical college and hospital, Pilakhuwa, Uttar Pradesh India. Participant received Jatamayadi Kashaya shirodhara and Mantra Music (Gayatri Mantra) was played simultaneously during the therapy for managing pre-hypertension. Findings: The findings suggest that the concurrent application of Jatamayadi Shirodhara and Mantra Music resulted in a significant reduction in systolic and diastolic blood pressure readings, alongside improvements in heart rate variability and subjective stress levels, indicating the potential efficacy of this combined Ayurvedic approach in managing pre-hypertension. Implication: This integrative protocol offers a non-pharmacological therapeutic strategy that may mitigate the progression of pre-hypertension by addressing autonomic dysfunction and psychological stress, thereby reducing the long-term risk of cardiovascular morbidity. Originality/Value: This study contributes to the existing literature by providing the first documented evidence of the synergistic effects of combining Jatamayadi Shirodhara with Mantra Music, offering a novel, non-invasive protocol for pre-hypertension management that aligns with the holistic principles of Ayurvedic personalized medicine.